2005
DOI: 10.1088/0953-8984/17/15/020
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase transition and dielectric relaxation in Pb(Zn1/3Nb2/3)O3single crystals

Abstract: The structure and the dielectric properties of Pb(Zn 1/3 Nb 2/3 )O 3 (PZN) crystal have been investigated by means of high-resolution synchrotron xray diffraction (with an x-ray energy of 32 keV) and dielectric spectroscopy (in the frequency range 100 Hz-1 MHz). At high temperatures, the PZN crystal exhibits a cubic symmetry and polar nanoregions inherent to relaxor ferroelectrics are present, as evidenced by the single (222) Bragg peak and by the noticeable tails at the base of the peak. At low temperatures, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 43 publications
5
29
1
4
Order By: Relevance
“…On the larger length scale, there is some controversy on the average structure of these systems. From conventional x-ray diffraction measurements, 29,30 it was believed that PZN shows a diffuse transition to the rhombohedral phase below 390 K, which is slightly lower than the peak temperature in the dielectric constant. On the other hand, high-energy x-ray diffraction studies 31 found no evidence of rhombohedral distortion down to much lower temperatures.…”
Section: A Thermal Conductivitymentioning
confidence: 99%
“…On the larger length scale, there is some controversy on the average structure of these systems. From conventional x-ray diffraction measurements, 29,30 it was believed that PZN shows a diffuse transition to the rhombohedral phase below 390 K, which is slightly lower than the peak temperature in the dielectric constant. On the other hand, high-energy x-ray diffraction studies 31 found no evidence of rhombohedral distortion down to much lower temperatures.…”
Section: A Thermal Conductivitymentioning
confidence: 99%
“…Recently, it was found that a sharp phase transition at 114 • C below the paraelectricferroelectric phase transition point appears in PZN under the conditions of the zero-field heating (ZFH) after a preceding field cooling (FC) [18][19][20][21], implying that decrease of heterogeneity owing to the applied electric field on the FC may make the phase transition sharp, which is usually smeared by the complex domain structures such as PNRs. The critical slowing down and temperature dependences of the second-and third-order nonlinear dielectric constants near this transition point were reported [22].…”
Section: /[1066]mentioning
confidence: 99%
“…Relaxor ferroelectrics have attracted tremendous attention in recent years because of their extraordinary dielectric and piezoelectric properties (Park & Shrout, 1997). Of these materials, the lead-based perovskite relaxor, Pb(Zn 1/3 Nb 2/3 )O 3 (PZN) has been one of the most extensively studied (Ye et al, 1999;Bing et al, 2005). Despite this, the exact nature of the structure and how it relates to its relaxor properties is still the subject of much controversy.…”
Section: Example 2: Polar Nanodomains In Pbzn 1/3 Nb 2/3 Omentioning
confidence: 99%